Pengaruh Kedisiplinan Dan Loyalitas Karyawan Terhadap Prestasi Karyawan PT. XYZ Kota Medan - Walyono Walyono; Neni Triastuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Discipline is the most important operative function of human resource management, because the better the employee discipline in the company, the higher the work performance that can be achieved. Furthermore, in a company, in addition to work discipline, work loyalty also has an important role in the management of human resources which in general can be interpreted as a form of loyalty, devotion and trust given or shown to the company, in which there is a sense of belonging and trying to provide services. and best behavior. The purpose of this study was to determine the effect of discipline and loyalty on the work performance of employees of PT. XYZ Medan City. The population in this study were permanent employees of PT. XYZ Medan City has 40 employees. From the results of the partial test (t test) of the work discipline variable (X1) on the work performance variable (Y) and based on the criteria of the T test, obtained a significance of 0.221> 0.05 and the value of t count = 1.246 < t table = 2.024, then Ho is accepted, it can be partially concluded that there is no effect of work discipline on work performance at PT. XYZ Medan City. From the results of the partial test (t test) of the loyalty variable (X2) on the work performance variable (Y) and based on the criteria of the T test, obtained a significance of 0.00 > 0.05 and the value of t count = 5.575 > t table = 2.024, then Ho rejected, it can be partially concluded that there is an influence of loyalty on work performance at PT. XYZ Medan City. From the results of data processing, obtained a significance value of 0.0 which is smaller than 0.05. From this analysis, Ho is rejected, meaning that there are simultaneously independent variables affecting the dependent variable. To improve employee performance, employee discipline and employee loyalty must also be improved.